Contact allergy to ingredients of hair cosmetics - a comparison of female hairdressers and clients based on IVDK 2007-2012 data - Uter, Wolfgang; Gefeller, Olaf; John, Swen Malte; Schnuch, Axel; Geier, Johannes (Contact Dermatitis, 2014)
Cosmetics for bleaching, waving/relaxing and dyeing hair contain well-known allergens, leading to a substantial number of cases of allergic contact dermatitis.To compare the frequency of important contact allergens (i) between two distinct groups of exposed patients, and (ii) with previous surveillance data.On the basis of data collected by the Information Network of Departments of Dermatology (IVDK; www.ivkd.org) between 2007 and 2012 in 824 female hairdressers and 2067 female clients, the current spectrum of contact sensitization to ingredients of hair cosmetics, as contained in different pertinent series, is described.A similar burden of sensitization as in previous analyses was observed, but with some increase in sensitization to oxidative hair dye components in clients. Some allergens mainly affected hairdressers, such as ammonium persulfate (18.7% positive) and glyceryl monothioglycolate (GMTG; still 4.7% positive, with a few cases also in young hairdressers, despite removal from the German market).Hair dyes remain important contact allergens, despite various attempts by the cosmetic industry to introduce hair dyes with lower allergenic potential. The re-emergence of GMTG as an occupational allergen should be considered as a warning signal ('sentinel event') prompting close monitoring.
EVALuna2:5458